Efektivitas Metode Pembelajaran Team Quiz Pada Mata Pelajaran IPA Materi Fisika Peserta Didik Kelas VIII SMP Negeri 10 Kerinci - Dwitri Pilendia; Enny Zarvianti; Jeki Umbara (Peneliti.net, 2023)
This study aims to determine the effectiveness of the team quiz learning method in the physics subject for class VIII students of SMP Negeri 10 Kerinci. This type of research is experimental research with a pre-experimental form, the design of the research design is One Group Pretest Posttest Design. The population in this study were all 82 class VIII students of SMP Negeri 10 Kerinci, consisting of 37 male students and 45 female students. From the learning outcomes obtained from the final test after learning, based on the normality and homogeneity tests of the learning outcomes data for one class of the sample, it was found that the data were normally distributed and homogeneous, so the t-test was used to test the hypothesis. From the calculation results, the average posttest result = 78.61 while the average pretest result = 46.19. Because ????ℎ????????????????????= 21.16 and ????????????????????????= 1.71 means ????0 is rejected and ????1 is accepted. So it can be concluded that there is effectiveness of the team quiz learning method in the physics subject for class VIII students of SMP Negeri 10 Kerinci in the 2020/2021 academic year.